Endometriosis in para-aortic lymph node resembling a malignancy: a case report and literature review - Jinjin Li; Yingwei Liu; Kaiwen Du; Lin Xiao; Xinyue He; Fengqin Dai; Junying Tang (BMC, 2022)
Abstract Background Endometriosis is a common benign gynecological disease characterized by growing-functioning endometrial tissue outside the uterus. Extra-pelvic endometriosis, which accounts for approximately 12% of endometriosis, is more challenging to diagnose because of its distance from the pelvic organs. Halban's theory of benign metastasis indicates that endometrial cells can appear in extra-pelvic organs via lymphatic and blood vessels, but endometrial lymph node metastasis cases are still rare. We report a case of endometriosis in a para-aortic lymph node whose clinical behavior mimicked a malignancy. Case presentation A 52-year-old perimenopausal woman underwent laparoscopic hysterectomy plus bilateral salpingectomy (the patient insisted on the preservation of her ovaries) at a local hospital 2 years earlier because of adenomyosis. The patient presented with a complaint of low back pain to the gastrointestinal outpatient department of our hospital. The carbohydrate antigen 125 (CA125) was abnormally elevated at 5280.20 U/ml, human epididymis 4 (HE4) was 86.0 pmol/L, while other tumor markers were normal. Serum female hormone results were in the postmenopausal range, and her gastroenteroscopy showed no abnormalities. Moreover, both enhanced magnetic resonance imaging and positron emission tomography-computed tomography showed a high possibility of a retroperitoneal malignant lymph node (metastasis possible, primary site unknown). One week after admission, she underwent laparoscopic exploratory surgery, during which we observed normal shape and size of both ovaries while the left ovary was cystic-solid. After opening the retroperitoneal space, an enlarged lymph node-like tissue measuring 8 × 4 × 3 cm3 was found near the abdominal aorta. When the surrounding adhesions were separated, lymph node-like tissue was poorly demarcated from the abdominal aorta and renal artery. Some lymph node samples and left ovary were sent for intraoperative frozen section, which revealed benign lesions, similar to endometrial tissue. The lymph node tissue was then excised as much as possible, and the second set of intraoperative frozen sections showed high probability of endometrial tissue. The final histopathology and immunohistochemistry staining reached a diagnosis of para-aortic lymph node endometriosis. Gonadotropin-releasing hormone antigen treatment was recommended every 28 days because of the high preoperative CA125 and imaging-based suspicion of malignancy. The serum CA125 subsequently decreased to normal levels, and no para-aortic lesions were detected on abdominal enhancement CT. She is being followed up regularly. Conclusion It is known that the incidence of lymph node metastasis in pelvic endometriosis is relatively rare. Our report shows that endometriotic tissue can metastasize via the lymphatic route and suggests that endometriotic tissue has the characteristics of invasion and metastasis.